Insights on the Evolution of Prolyl 3-Hydroxylation Sites from Comparative Analysis of Chicken and Xenopus Fibrillar Collagens - Hudson, David M. (Public Library of Science, 2011)
Recessive mutations that prevent 3-hydroxyproline formation in type I collagen have been shown to cause forms of osteogenesis imperfecta. In mammals, all A-clade collagen chains with a GPP sequence at the A1 site (P986), except α1(III), have 3Hyp at residue P986. Available avian, amphibian and reptilian type III collagen sequences from the genomic database (Ensembl) all differ in sequence motif from mammals at the A1 site. This suggests a potential evolutionary distinction in prolyl 3-hydroxylation between mammals and earlier vertebrates. Using peptide mass spectrometry, we confirmed that this 3Hyp site is fully occupied in α1(III) from an amphibian, Xenopus laevis, as it is in chicken. A thorough characterization of all predicted 3Hyp sites in collagen types I, II, III and V from chicken and xenopus revealed further differences in the pattern of occupancy of the A3 site (P707). In mammals only α2(I) and α2(V) chains had any 3Hyp at the A3 site, whereas in chicken all α-chains except α1(III) had A3 at least partially 3-hydroxylated. The A3 site was also partially 3-hydroxylated in xenopus α1(I). Minor differences in covalent cross-linking between chicken, xenopus and mammal type I and III collagens were also found as a potential index of evolving functional differences. The function of 3Hyp is still unknown but observed differences in site occupancy during vertebrate evolution are likely to give important clues.